Free Will and Counterculture Movement in Anthony Burgess’ A Clockwork Orange - Dewi Pusparini; Burhanuddin Arafah; Herawaty Abbas (Hasanuddin University, 2018)
This research explores the relation between the aspect of free will in the novel A Clockwork Orange to the social and cultural phenomena in the era of counterculture movement. The writer uses descriptive qualitative method to analyze the structural elements of the novel and relate them to the supporting data from external references. The objectives of the research which are presented as follows: 1) to describe the way the importance of free will affect the characters’ behavior in A Clockwork Orange, and 2) to reveal the way the importance of free will in this novel reflect the social condition during the era of counterculture movement. The writer also applies the genetic structuralism approach to focus the analysis on the element of free will and the way it relates to the elements of counterculture. The result of this research shows that there are several structural relations that connect both the aspect of free will in the novel and those in the era of counter-culture movement which consist of youth subculture, resistance against the state, and police brutality. The implication of this research is to promote the improvement of youth’s behavior and social awareness by the implementation of free will and safe environment, not by force or violence.